Pembagian Harta Waris pada Masyarakat Awo’: Perspektif Hukum Kewarisan Islam - Alwi, Mujahid; Shuhufi, Muhammad; Amin, Abd. Rauf Muhammad (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Inheritance in Islam has principles, procedures, and things that need to be fulfilled. The division of inheritance must be done fairly and transparently to avoid inheritance disputes. However, in Indonesia, the customary inheritance system has been used since long ago and has become a tradition, but most people already understand how the Islamic inheritance system works. The purpose of this discussion is to examine the inheritance distribution system in the awo’ community, from the perspective of Islamic law. This research is qualitative research. The data collection method used in this research is by conducting field observations, interviews, and literature review. This research emphasizes the division of inheritance property in awo’ society. This research aims to find out how the application of the division of inheritance property in awo’ society from the perspective of Islamic law and customary law. In addition, this research also aims to find out the advantages and disadvantages that exist in the application of the inheritance system.